H-ATLAS: the far-infrared properties of galaxies in and around the Coma cluster - Fuller, C.; Davies, J.I.; Smith, M.W.L.; Valiante, E.; Eales, S.; Bourne, N.; Dunne, L.; Dye, S.; Furlanetto, C.; Ibar, E.; Ivison, R.J.; Maddox, S.; et al. (Oxford University Press, 2016)
We describe a far-infrared survey of the Coma cluster and the galaxy filament it resides within. Our survey covers an area of ∼150 deg2 observed by Herschel H-ATLAS (Herschel Astrophysical Terahertz Large Area Survey) in five bands at 100, 160, 250, 350 and 500 μm. The SDSS spectroscopic survey (mr ≤ 17.8) is used to define an area (within the virial radius) and redshift selected (4268 < v < 9700 km s−1) sample of 744 Coma cluster galaxies – the Coma Cluster Catalogue. For comparison, we also define a sample of 951 galaxies in the connecting filament – the Coma Filament Catalogue. The optical positions and parameters are used to define appropriate apertures to measure each galaxy's far-infrared emission. We have detected 99 of 744 (13 per cent) and 422 of 951 (44 per cent) of the cluster and filament galaxies in the SPIRE 250 μm band. We consider the relative detection rates of galaxies of different morphological types finding that it is only the S0/Sa population that shows clear differences between the cluster and filament. We find no differences between the dust masses and temperatures of cluster and filament galaxies with the exception of early-type galaxy dust temperatures, which are significantly hotter in the cluster than in the filament (X-ray heating?). From a chemical evolution model, we find no evidence for different evolutionary processes (gas loss or infall) between galaxies in the cluster and filament.